Implementation of Pancasila Ideology in Modern Society - Kurniawan, Ericka Kesya; Wilsen, Vetrick; Valencia, Shanty; Azizah, Qonita (Jurnal Pendidikan Amartha, 2022)
The challenge in implementing Pancasila is due to the globalization of new thinking that is very contrary or distorted to the values and ideology of Pancasila because of the influx of foreign cultures that can increasingly erode the indigenous culture of Indonesia. The development of technology is the biggest influence in changing people's personality and behavior today so that Pancasila is now starting to be further eroded by the process of modernization and globalization. The purpose of this study is to implement the ideology of Pancasila in modern society. The research method used is a qualitative method with techniques in the form of observations of cases that currently occur in modern society related to the current implementation of pancasila. This discussion is related to the implementation of Pancasila in this modern era, which is carried out by instilling Religious education and civic education as well as conducting and socializing Pancasila values so that modern society does not forget and can continue to maintain the identity of the Indonesian nation.